Interspecific P.crispum varieties and hybrids perspective for subtropics of Russia - N. M. Gutieva (Новые технологии)
The possibility of creating new modern genotypes of Pelargonium L.Her.ex Ait. genus by method of interspecific hybridization. Economically valuable recombinants and promising combinations of crosses have been outlined and promising forms have been highlighted. P.crispum varieties resistant to extreme environmental factors of humid subtropics of the south of the Krasnodar Territory have been obtained for the first time. Five varieties of P.crispum are registered in the State Register of Breeding Achievements of the Russian Federation.